Analgesic effects and possible mechanisms of iridoid glycosides from Lamiophlomis rotata (Benth.) Kudo in rats with spared nerve injury. (15th September 2015) - Zheng, Yanan; Yin, Xuefei; Huo, Fuquan; Xiong, Hui; Mei, Zhinan
Abstract: Ethnopharmacological relevance: Lamiophlomis rotata (Benth.) Kudo ( L. rotata ) is a medical plant that has been traditionally used for centuries for the treatment of pain, such as bone and muscle pain, joint pain and dysmenorrhea. Although iridoid glycosides of L. rotata (IGLR) are the major active components of it according to reports, it still remains poorly understood about the molecular mechanisms underlying analgesic effects of IGLR. The aim of the present study was to investigate the analgesic effect of IGLR on a spared nerve injury (SNI) model of neuropathic pain. Materials and methods: The SNI model in rats was established by complete transection of the common peroneal and tibial distal branches of the sciatic nerve, leaving the sural branch intact. Then SNI rats were treated with IGLR for 14 days, using normal saline as the negative control. The paw withdrawal mechanical threshold (PMWT) in response to mechanical stimulation was measured by von Frey filaments on day 1 before operation and on days 1, 3, 5, 7, 9, 11, 13 and 14 after operation, respectively. After 14 days, the levels of nitric oxide (NO), nitric oxide synthase (NOS), tumor necrosis factor- α (TNF- α ), interleukin-1β (IL-1β), interleukin-10 (IL-10) and cyclic guanosine monophosphate (cGMP) in the spinal dorsal horn were measured by the corresponding kits, mRNA expression of inducible NOS (iNOS) and protein kinase G type I (PKGI) of spinal cord were analyzed by reverse-transcription polymerase chain reaction (RT-PCR). The expression of N-methyl-D -aspartate receptor (NMDAR) and protein kinase C (PKCγ) of the spinal dorsal horn was performed by Western blot. Before all the experiments, motor coordination performance and locomotor activity had been tested. Results: Our results showed that remarkable mechanical allodynia was observed on day 1 after operation in the SNI model, which was accompanied by a decrease in PMWT. Treatment with IGLR (200, 400, 800 mg/kg) significantly alleviated SNI-induced mechanical allodynia, markedly decreased the levels of NO, NOS, TNF- α, IL-1β and cGMP, and increased the level of IL-10. Meanwhile, IGLR (200, 400, 800 mg/kg) also inhibited the protein expression of NMDAR, PKCγ and the mRNA expression of iNOS and PKGΙ in the spinal cord. In addition, gavage with the IGLR aqueous extract (800 mg/kg) did not signifiantly alter motor coordination or locomotor activity. Conclusions: These results indicated IGLR could produce an anti-neuropathic pain effect that might partly be related to the inhibition of the NO/cGMP/PKG and NMDAR/PKC pathways and the level of TNF- α, IL-1β as well as to the increase of the level of IL-10 in spinal cord. Graphical abstract: